2001
DOI: 10.1016/s0006-3495(01)75760-8
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a Polytopic Membrane Protein Structure from the Solution Structures of Overlapping Peptide Fragments of Bacteriorhodopsin

Abstract: Three-dimensional structures of only a handful of membrane proteins have been solved, in contrast to the thousands of structures of water-soluble proteins. Difficulties in crystallization have inhibited the determination of the three-dimensional structure of membrane proteins by x-ray crystallography and have spotlighted the critical need for alternative approaches to membrane protein structure. A new approach to the three-dimensional structure of membrane proteins has been developed and tested on the integral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 45 publications
5
81
1
Order By: Relevance
“…Therefore, it is reasonable to presume that they would also be favorable within the setting of the NHE1 protein. Indeed, a number of studies have demonstrated strong correspondence between structures of peptides or protein segments obtained in membrane mimetic solvents to structures obtained by solution state NMR in micelles or to entire membrane proteins determined by x-ray crystallography (11)(12)(13). Most interestingly, we find that CD 3 OH:CDCl 3 :H 2 O provides a well defined peptide structure, whereas the peptide in Me 2 SO appears much less structured.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Therefore, it is reasonable to presume that they would also be favorable within the setting of the NHE1 protein. Indeed, a number of studies have demonstrated strong correspondence between structures of peptides or protein segments obtained in membrane mimetic solvents to structures obtained by solution state NMR in micelles or to entire membrane proteins determined by x-ray crystallography (11)(12)(13). Most interestingly, we find that CD 3 OH:CDCl 3 :H 2 O provides a well defined peptide structure, whereas the peptide in Me 2 SO appears much less structured.…”
Section: Discussionmentioning
confidence: 50%
“…This provides insight into structured regions, in our case, without fixing the segment as a whole into a single conformation. The use of solution conditions having a low dielectric constant to mimic a membrane environment has become quite common for structural studies of transmembrane proteins or peptides and has provided structures of isolated protein segments consistent with their structures in the full protein (11)(12)(13). Our study demonstrates that whereas TM IV is structured, only a 4 -6-residue stretch of the segment is helical.…”
mentioning
confidence: 52%
“…Earlier studies have demonstrated that the amino acid sequences of TM segments of membrane proteins contain most of the required structural information needed to form their native structures (55)(56)(57)(58). This approach has been used successfully previously for mammalian NHE1 (15,16) and for the membrane domain of CorA (59).…”
Section: Discussionmentioning
confidence: 99%
“…It must be acknowledged that an isolated membrane segment could have a different structure than that found in an intact membrane protein. However, isolated TM segments from membrane proteins having multiple TM segments, including the cystic fibrosis transmembrane conductance regulator (17,18), bacteriorhodopsin (19,20), rhodopsin (21), and the fungal G-protein-coupled receptor Ste2p (22), have been shown to be both functional and to have structures in good agreement with the segments in the context of the entire protein, where available. An important caveat is that solution conditions may need extensive screening in order to achieve stabilization of the peptide in its physiological structure, for example, the variation in bacteriorhodopsin results of Ref.…”
Section: The Atomic Coordinates and Structure Factors (Code 2htg) Havmentioning
confidence: 99%